Analisis Eksploratif Praktik Online Child Sexual Exploitationand Abuse (OCSEA) dalam Interaksi Roleplay Virtual - Fadiani Risqita Mamang; Gaby Valenia Rosa Purba; Nafisa Spica Diraelanabil; Mardhatillah Syahrani Fauziah; Maria Vanessa Ferdianto; Herdina Indrijati (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
The phenomenon of transitioning from roleplay to sexplay in virtual spaces indicates a hidden form of Online Child Sexual Exploitation and Abuse (OCSEA). This study aims to identify forms of OCSEA, victims' coping strategies, and the relationship between OCSEA and child sexual addiction. An exploratory sequential design with mixed methods was used to explore the phenomenon and develop the Digital Roleplay Sexual Addiction Scale (SAS-RD) for quantitative measurement. The qualitative stage was conducted through semi-structured interviews with children aged 15–17 years, followed by a quantitative stage using the Digital Roleplay Sexual Addiction Scale (SAS-RD) with 405 respondents using purposive sampling based on the Lemeshow formula. Correlation tests showed a significant relationship between OCSEA and sexual addiction (Spearman = 0.837) and a positive influence on digital sexual addiction (R2 = 0.814). These findings confirm that virtual roleplay can reinforce children's sexual addiction, thus requiring intervention strategies as a preventive measure.